Translation and Interpreting Studies education in the midst of platform capitalism - Sahin, Mehmet; Oral, Sevket Benhur (The Journal of Specialised Translation, 2021)
In this study, we examine how TIS education unfolds within an all-encompassing digital education context that has been dramatically intensified by the sudden switch over to online-only instruction during the COVID-19 pandemic in major universities in Turkey. We surveyed 17 instructors (four were later interviewed) and 46 undergraduate students in order to find out how pedagogical relationships are impacted by the online-only distance education modalities. The disruptive effects as well as emancipatory potentials of these changes for TIS pedagogy were probed. In addressing these issues, the conceptual framework of the threefold division of educational purposes into qualification, socialisation, and subjectification was deployed. The analysis of our data suggests a lack of concerted attempts to address subjectification as a central issue in the online-only learning environment in TIS education. Both instructors and students have concerns regarding the domain of subjectification. Yet, instructors seem mostly focused on qualification- and socialisation-related issues rather than the needs of their students in terms of their subjectification. In this context, the so-called platform capitalism promotes pedagogical relationships that are not conducive to fostering the domain of subjectification and therefore poses a risk to the development of students' personal and professional identity.